Clinical application of genomic profiling to find druggable targets for adolescent and young adult (AYA) cancer patients with metastasis. Issue 1 (December 2016) - Cha, Soojin; Lee, Jeongeun; Shin, Jong-Yeon; Kim, Ji-Yeon; Sim, Sung; Keam, Bhumsuk; Kim, Tae; Kim, Dong-Wan; Heo, Dae; Lee, Se-Hoon; Kim, Jong-Il
Abstract Background Although adolescent and young adult (AYA) cancers are characterized by biological features and clinical outcomes distinct from those of other age groups, the molecular profile of AYA cancers has not been well defined. In this study, we analyzed cancer genomes from rare types of metastatic AYA cancers to identify driving and/or druggable genetic alterations. Methods Prospectively collected AYA tumor samples from seven different patients were analyzed using three different genomics platforms (whole-exome sequencing, whole-transcriptome sequencing or OncoScan™). Using well-known bioinformatics tools (bwa, Picard, GATK, MuTect, and Somatic Indel Detector) and our annotation approach with open access databases (DAVID and DGIdb), we processed sequencing data and identified driving genetic alterations and their druggability. Results The mutation frequencies of AYA cancers were lower than those of other adult cancers (median = 0.56), except for a germ cell tumor with hypermutation. We identified patient-specific genetic alterations in candidate driving genes:RASA2 andNF1 (prostate cancer), TP53 andCDKN2C (olfactory neuroblastoma), FAT1, NOTCH1, andSMAD4 (head and neck cancer), KRAS (urachal carcinoma), EML4-ALK (lung cancer), andMDM2 andPTEN (liposarcoma). We then suggested potential drugs for each patient according to his or her altered genes and related pathways. By comparing candidate driving genes between AYA cancers and those from all age groups for the same type of cancer, we identified different driving genes in prostate cancer and a germ cell tumor in AYAs compared with all age groups, whereas three common alterations (TP53, FAT1, andNOTCH1 ) in head and neck cancer were identified in both groups. Conclusion We identified the patient-specific genetic alterations and druggability of seven rare types of AYA cancers using three genomics platforms. Additionally, genetic alterations in cancers from AYA and those from all age groups varied by cancer type.